พัฒนาการของการรับรองสิทธิและการจำกัดสิทธิในทรัพย์สินในระบบกฎหมายไทย - สุนันทา ดาราศร (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Property rights are a fundamental right for all of mankind. This right belongs to all men by the nature, not the state. By holding this right, that mean we are free with fully liberties. No one can take these rights from another. Thailand has guarantee property right as a fundamental rights since 2475 B.E. when the 1st constitution of the kingdom of Thailand enforced until nowadays. According to the study about a development of property rights and its restriction under the Thai legal system by this thesis, Thailand places the scope of accreditation and restrictions of this right under the word "Duty to Public". To do that, Legislator in Thailand uses all kinds of law to guarantee and restrict the right in the same time. By the doses of law that was designed to restrict the way that people exercise property rights, Expropriation is one of the legal mechanism that mostly use to restrict the right of the people. Government or authorities, all way use the word "For the development of the country" when they ask people to disclaim the right by the whole or some part of it. This kind of control or restrict for development seem to expand to all kinds of property with more and more control. By expanded of the restriction, State officer or the authority must beware and more be careful when decide to use all of the restriction mechanism to the right of the people. And if the legislator have to establish new law, They have to carefully consider that law to meet all of the necessary conditions laid down by the constitution and compare it with another country like Germany. They have to aware that "Whatever the circumstances, Restrictions on basic rights as prescribed by the Constitution. Must have no effect on the content or substance of the right to liberty.